Absolute alterity: E. Levinas and J. Derrida - Bacevičiūtė, Danutė (Religija ir kultūra, 2007)
The article deals with a notion of absolute alterity in E. Levinas and J. Derrida. It questions the origin of that notion by stressing its temporal aspect. The “phenomenon” of death as absolute alterity allows to find out here at work both phenomenological and speculative strategies. The article shows position of Levinas as the junction of these two strategies. It presents in detail speculative moment of Levinas thought, which usually slips researchers’ attention, discusses the “dialectic”, which allows to move from the absolute alterity of death to the absolute alterity of other person in ethical relation. Derrida reads Levinas’ claim for absolute alterity in horizon of finitude: every other (one) is every (bit) other. In response to uniqueness of the event deconstruction appears as interpretative, aporetical experience. That means that it must take place in the interval that separates calculation and incalculable, universality and singularity. So it is experience of the undecidable. The article investigates Derrida’s strategy of deconstructive reading and raises the question: does not the deconstruction itself take the place of undeconstructible alterity (absolute alterity)?